Language as a mental capacity - Hillert, Dieter (Frontiers in Language Sciences, 2026)
While bonding and stress signals are widespread across species, symbolic computation is a uniquely human capacity. This article examines the intricate relationship between the evolving primate brain and the emergence of the mental language capacity in the human lineage, focusing on the neural circuits instantiated by mental agents. By integrating neurobiological and eco-cultural evidence, we identify a punctuated step at around 1.8 Ma with the appearance of Homo erectus and propose a corresponding neural threshold for symbolic representations and processes. The critical increase in internal computational capacity may reflect interactions between behavioral dynamics and neurogenetic properties. We argue, in particular, that the rise in social interactions and learning, the adoption of an energetically richer diet, and increased mobility exerted mutually reinforcing effects on cortical reorganization, enhancing neural connectivity and ultimately supporting symbolic language processing. We therefore suggest a scaled mental capacity for language and emphasize the importance of incorporating neurobiological factors when defining the evolution of the language capacity and its functions.